Reconciling transfer synchronization and service regularity: real-time control strategies using passenger data. Issue 2 (29th November 2019) - Gavriilidou, Alexandra; Cats, Oded
ABSTRACT: Real-time holding control strategies are implemented, among other reasons, in order to protect transfers. In the context of high-frequency services, there is a need to reconcile between striving for single-line regularity and synchronizing inter-line arrivals. Their operationalization depends on the predictions regarding passenger flows across the network. We examine the influence of real-time passenger data on the performance of transfer synchronization control. To this end, we develop two real-time transfer synchronization controllers which make use of different passenger data sources. The controllers differ in their assumptions concerning capacity constraints as well as on-board crowding conditions. The results show that each transferring passenger saves on average 2–10 min thanks to the proposed strategy, while on-board passengers experience a delay of 1–2 min each in most cases. The highest time saving per transferring passenger is obtained when the demand level is low and the controller opts for synchronizing more frequently. Highlights Rule-based holding controller selects transfer synchronization or line regularity The impact of different passenger data on controller performance is investigated On-board crowding conditions are considered by the real-time controller On-board occupancy is the most valuable real-time passenger data source